Oral Health: The First Step to Well-Being - Fiorillo, Luca (Medicina (Kaunas), 2019)
Scientific research in the medical field shows this constantly: health starts from the mouth. Having good oral health nowadays is not only aimed at tooth health, but as amply demonstrated in the literature, it is a starting point for the general health and well-being of our body. Retracing the latest scientific findings that demonstrate an interpolation between oral health, oral diseases, and systemic complications, literature support was brought to this manuscript. Oral health, as demonstrated, has potentially multi-organ systemic implications, and as the results of the recent literature demonstrate, these implications range from an insulin resistance, due to a periodontal disease, up to far more complex multi-organ systemic complications involving the cardiovascular system or even neurodegenerative pathology. Therefore, being able to improve oral health could have great systemic implications for the organism, for the prevention of pathologies, and therefore for society and for the quality of life in individuals.